Looking for Positive Viewpoints for Alzheimer's Caregivers: Case Evaluation of a Positive Energy Group. Issue 1 (March 2016) - Hsieh, Wenchien; Chen, Qinying; Sun, Qingling; Chen, Peixuan; Chen, Yijia; Xu, Wenting; Zhang, Yiting; Yu, Yiqian; Huang, Yimei
Objective: As estimated in a report of global Alzheimer's disease published by Alzheimer's Disease International in 2015, there will be 9.9 million new patients worldwide with Alzheimer's disease in 2015, with a new Alzheimer's patient diagnosed, on average, every 3 seconds. Since Alzheimer's disease is an irreversible disease, the most that can be done for Alzheimer's patients is to merely delay the onset of disease, which to date cannot be completely cured. Therefore, even though great effort is put into caring for the patient, caregivers should not expect any substantial changes. The caring process is a dynamic process that contains negative and positive experiences. During the caring period, not only do caregivers spend a lot of effort and work very hard to help the patient, but in fact care recipients themselves also give energy to caregivers. This study attempts to take a positive energy viewpoint to explore and design a program that is suitable for Alzheimer's caregivers. The aims of the study were as follows: (a) to explore the needs and burdens of Alzheimer's caregivers in the treatment process of patients, (b) to design a program that meets the needs of the caregivers, and (c) to evaluate the effects of implementing a program. Methods: The study is a qualitative study employing in-depth interviews. Interviews were conducted from September 2015 to December 2015; the interview results were reviewed and a positive energy group program was designed. Pre-test and post-test interviews were carried out for the program so as to evaluate the effects of the program. Results: According to the caregiver interview results, we understand the caring needs and caring process of caregivers. From the interview results, we now know that caregivers' continuous care mainly comes from positive energy in psychological, social and relationship aspects. Positive energy seems to have been affecting caregivers' caring ability and willingness. Therefore, a two-stage group activity program was designed to provide a recollective handmade craft group and an art therapy group. Research results of the study show that when the main caregivers of Alzheimer's patients took part in group activities, positive energy in social and relationship aspects increased for the caregiver group too. Conclusions: From these intervention programs caregivers could obtain more knowledge of patient care and these activities could effectively lighten caregivers' burdens.